HAMBATAN GURU MATEMATIKA DALAM PENERAPAN KURIKULUM 2013 DI SEKOLAH DASAR - Refnywidialistuti; Nurhizrah Gistituati; Alwen Bentri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
A curriculum is an educational design that has a position and influences educational activities. Changes from the KTSP curriculum to the 2013 curriculum influence teachers to experience obstacles to the implementation in the learning process. The 2013 curriculum includes five learning aspects; observation, question, collection, association, and communication. Students have learned mathematics at school. Mathematics learning is one of the learnings that can improve students’ logical thinking, analytical, systematic, critical, innovative, and creative skills, and can make students being cooperative in mathematics learning. This mathematics learning is assumed to be difficult to accept for students. Hence, this research is conducted to identify teachers' difficulties in arranging learning tools and activities. The results indicate that there are three activities in the teaching and learning processes in the 2013 curriculum, they are initial, core, and final activities. In the initial activity, the teacher has difficulty in designing lesson plans and allocating learning time. In the core activity, the teacher has difficulty making students focus on the teaching and learning process. In the final activity, the teacher has difficulty directing and helping students to make conclusions about the learning so it was difficult for the teacher to evaluate the learning proces.